2018
DOI: 10.1002/fsn3.672
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic potentials of Lactobacillus plantarum isolated from fermented durian (Tempoyak), a Malaysian traditional condiment

Abstract: Lactic acid bacterium isolated from fermented durian (tempoyak) was investigated for its potentials as a probiotic strain. Bacterial tolerance toward gastrointestinal environment, adhesion, and cytotoxic activity in human colon adenocarcinoma cell line HT‐29 was evaluated. 16S rRNA sequencing identified the lactic acid bacterium as Lactobacillus plantarum. The bacterium demonstrated good tolerance toward gastrointestinal pH 2.0 and 0.3% bile salts. It showed strong adhesive capacity in human intestinal cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…The LAB microorganisms were identified as Lactobacillus plantarum . However, other species including Lactobacillus fersantum, Lactobacillus corynebacterium, Lactobacillus brevis, Lactobacillus mali, Lactobacillus fermentum, Lactobacillus durianis, Lactobacillus casei, Lactobacillus collinoides, Lactobacillus paracasei and Lactobacillus fructivorans were also reported in Tempoyak [67,68,69,70]. Khalil et al (2018) and Ahmad et al (2018) recently demonstrated the potential of Tempoyak as a source of probiotics.…”
Section: Health Benefits Of Durianmentioning
confidence: 99%
See 1 more Smart Citation
“…The LAB microorganisms were identified as Lactobacillus plantarum . However, other species including Lactobacillus fersantum, Lactobacillus corynebacterium, Lactobacillus brevis, Lactobacillus mali, Lactobacillus fermentum, Lactobacillus durianis, Lactobacillus casei, Lactobacillus collinoides, Lactobacillus paracasei and Lactobacillus fructivorans were also reported in Tempoyak [67,68,69,70]. Khalil et al (2018) and Ahmad et al (2018) recently demonstrated the potential of Tempoyak as a source of probiotics.…”
Section: Health Benefits Of Durianmentioning
confidence: 99%
“…These strains were able to produce exopolysaccharide (EPS) and had great potency to withstand the extreme conditions, either at low pH 3.0, in 0.3% bile salts or in in vitro model of gastrointestinal conditions [69]. EPS has the prebiotic potential to positively affect the gastrointestinal (GIT) microbiome and may reduce cholesterol [70]. Ahmad et al (2018) isolated Lactobacillus plantarum from Tempoyak and showed good probiotic properties including acid and bile salt tolerance, antioxidative, antiproliferative effects, and remarkable adhesion on colon adenocarcinoma cell line (HT-29 cell lines) [71].…”
Section: Health Benefits Of Durianmentioning
confidence: 99%
“…In recent years, the knowledge of consumers about food ingredients and their associated health benefits has been considerably increased (Brouns & Vermeer, ). Therefore, there is a requirement for foodstuff production with health benefits and people are making a conscious attempt to include them in their diet, with the hopes of maintaining or increasing their life quality (Ahmad, Yap, Kofli, & Ghazali, ; Brouns & Vermeer, ). Functional foods are expressed as “foods that through specific beneficial physiological action, improve the health of the consumer” (Corbo, Albenzio, De Angelis, Sevi, & Gobbetti, ).…”
Section: Introductionmentioning
confidence: 99%
“…cremoris, Pediococcus pentosaceus, and Lactobacillus pentosus are some types of bacteria that are naturally found in curd (Wirawati et al (2019). Tempoyak, a natural fermentation product from Durian, is also a natural fermentation product (Juliyarsi et al (2018) and tempoyak also contains lactic acid bacteria that have the potential as probiotics (Hartini et al 2019 andAhmad et al 2018). In addition, there are also naturally occurring fish fermented products called Budu originating from West Sumatra.…”
Section: Introductionmentioning
confidence: 99%